Prevalence and Determinants of Smoking among the College Students in Selected District of Bangladesh (Bangladesh Medical Journal, 2009)
Cigarette smoking is an intractable public health problem that poses threat to the health of the entire population. Smoking is considered as the single largest risk factor for a variety of malignancies, including lung cancer. The prevalence of smoking is gradually increasing among the students in Bangladesh. Considering this view, this cross sectional study was conducted in a selected higher secondary college of Moulvibazar district under Sylhet division. The objectives of the study were to determine the proportion of current smokers and its determinants among the college students. A total of 719 students were interviewed using self administered questionnaire. The mean age (SD) of the students was 17.1 (SD 1.5) years ranging from 15 to 22 years. Majority of the respondents were male (57.4%) and 42.6% were female with male-female ratio of 1.3:1. Out of 719 students, 22% were current smokers and the rest 78% were non smokers. Half of the students reportedly mentioned that they started smoking due to peer pressure followed by curiosity (34%), to avoid anxiety and tension (28%), feeling of maturity (14%, symbol of manliness (9%) etc. The most frequent form of smoking was cigarette (56%) followed by Bidi (37%), Hukkah (6%) and 2% hand made cigarette. The mean age of starting smoking was 13(SD 2.9) years ranging from 9 to 20 years. More than one third (35%) of the student's father were smokers, whereas 11.5% of their brothers were smokers. Logistic analysis revealed that only age, sex and educational attainment appeared to be important predictors of smoking (p